2003
DOI: 10.1038/ncb1055
|View full text |Cite
|
Sign up to set email alerts
|

Discs-Large and Strabismus are functionally linked to plasma membrane formation

Abstract: During early embryogenesis in Drosophila melanogaster, extensive vesicle transport occurs to build cell boundaries for 6,000 nuclei. Here we show that this important process depends on a functional complex formed between the tumour suppressor and adaptor protein Discs-Large (Dlg) 1 and the integral membrane protein Strabismus (Stbm)/Van Gogh (Vang) 2,3 . In support of this idea, embryos with mutations in either dlg or stbm displayed severe defects in plasma membrane formation. Conversely, overexpression of Dlg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 38 publications
5
74
0
Order By: Relevance
“…In motile cells, this process is restricted to the leading edge of the cell . Visualization of exocytosis in polarized cells has revealed that the vertical growth of epithelia relies on the directed delivery of PGCs to the lateral surface of the columnar cells, where the tethering factors, such as mammalian exocyst or Drosophila DLG, reside Lee et al, 2003;. Similarly, the exocyst can define PGC docking sites in neurite growth cones of differentiating neurons (Vega and Hsu, 2001).…”
Section: Docking and Fusion Of Pgcs With Acceptor Membranesmentioning
confidence: 99%
“…In motile cells, this process is restricted to the leading edge of the cell . Visualization of exocytosis in polarized cells has revealed that the vertical growth of epithelia relies on the directed delivery of PGCs to the lateral surface of the columnar cells, where the tethering factors, such as mammalian exocyst or Drosophila DLG, reside Lee et al, 2003;. Similarly, the exocyst can define PGC docking sites in neurite growth cones of differentiating neurons (Vega and Hsu, 2001).…”
Section: Docking and Fusion Of Pgcs With Acceptor Membranesmentioning
confidence: 99%
“…Rac1 is a downstream component of the Egfr pathway and acts antagonistically to Rho in order to regulate germ cell encapsulation; moreover, Rho activation perturbates TJ function in various experimental systems (Fischer et al 2007). It has already been shown that Dlg regulates membrane proliferation in a subset of NMJs in a dose-dependent fashion (Budnik et al 1996) and is an important player in the process of polarized membrane insertion during cellularization (Lecuit and Wieschaus 2000, Dudu et al 2004, Strickland and Burgess 2004, Lee et al 2003. The fact that membrane proliferation is also involved in mechanisms such as tissue spreading and cell surface extensions, including membrane ruffles (Lecuit andPilot 2003, Albertson, Riggs andSullivan 2005) and combined with our results on SCCs membrane ruffling upon Dlg overexpression, could mean that polarized membrane insertion, mediated by Dlg, might conduct SCCs growth, expansion and spreading over the germ cells of testicular cysts.…”
Section: Dlg Scrib and Lgl In The Drosophila Testismentioning
confidence: 99%
“…dlg, scrib and lgl are essential for planar cell polarity (PCP), by establishing a cross-talk between apical-basal and planar cell polarity. Dlg and Scrib have been shown to bind components of the core PCP machinery, including Frizzled receptors and the membrane protein Strabismus/Van Gogh (Stbm/Vang) (Montcouquiol et al 2006, Kallay et al 2006, Lee et al 2003, Hering and Sheng 2002. The direct interaction of Dlg4 with receptors of the Wnt signaling pathway, Frizzled 1-7, link mammalian Dlg to the Frizzled signaling (Humbert et al 2003, Hering andSheng 2002).…”
Section: Dlg Scrib and Lgl In Planar Cell Polaritymentioning
confidence: 99%
See 2 more Smart Citations